Analisis Daya Saing Ekspor Indonesia Produk Kopi panggang ke Kawasan ASEAN Berdasarkan Metode Revealed Comparative Advantage - Favian Jihan Prastian; Farida Pulansari (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Export means transporting or bringing goods and services from one country to another coun-try. In order to evaluate how strong export competitiveness is and identify market opportunities, specific calculation methods and approaches regarding comparative advantage are needed. One of them is using the